Learning from the Earthquake Nation: Japanese Science Diplomacy in the Twentieth Century. (July 2021) - Jacoby, Julia Mariko
Earthquake sciences, such as seismology and earthquake engineering, were important for Japanese science diplomacy throughout the twentieth century and remain relevant for Japan's science diplomacy initiatives today. This article traces how the earthquake sciences were constructed as a 'Japanese science', giving Japan authority in science diplomacy, what science diplomacy practices scientists engaged in, and the images of Japan they helped to convey internationally. In the late nineteenth century, Japan played a crucial role in establishing seismology as a scientific discipline, which supported claims of Japanese research experience with their highly seismically active environment. Thus, Japanese earthquake specialists were enabled to act on equal terms with their Western counterparts in international networks, and even became regarded as 'teachers' of earthquake-proof construction. This image that was built and expanded upon by generations of scientists and maintained regardless of the shifting political climate. Consequently, prewar science diplomacy served to justify 'civilised' Japanese colonial rule in East Asia, while postwar earthquake science underlined Japan's new identity as a peaceful 'developed' country and became a crucial part of Japan's developmental aid programs. Science diplomacy also helped open diplomatic channels for Japan during difficult international conditions and created sustainable networks between seismic countries.